Effects of Hormone Replacement Therapy on Coagulation, Fibrinolysis, and Thrombosis Risk in Postmenopausal Women - Koh, Kwang Kon; Horne, McDonald K., III; Cannon, Richard O., III (Thrombosis and Haemostasis, 1999)
In the United States and other developed countries, more women die from cardiovascular disease than from any other disease. The Nurses’ Health Study, among others, has suggested that postmenopausal women who take estrogen therapy have fewer cardiovascular events over time compared with untreated women.1,2 The favorable effects of orally-administered estrogen on lipoprotein levels, namely reductions in low-density lipoprotein (LDL) cholesterol and lipoprotein(a) levels, and increases in high-density lipoprotein (HDL) cholesterol levels, likely account for much of this apparent benefit. These effects have not yet, however, been proven in randomized clinical trials. Because estrogen has a multitude of biological effects, many other potential mechanisms by which estrogen provides protection against atherosclerosis and its consequences are currently being studied.Atherosclerosis is associated with chronic inflammation in response to injury and with a number of risk factors, such as elevated serum cholesterol, smoking, diabetes, and hypertension.3 Local activation of platelets and thrombus formation adjacent to atheromatous plaques, especially where ruptured or eroded, is now recognized to be of pathophysiological importance in the acute and chronic clinical expression of this disease.4 Thus, the favorable effects of estrogen on hemostasis may be relevant to the progression of atherosclerosis and associated clinical manifestations.In this regard, several groups have reported on the favorable effects of hormone replacement therapy on fibrinolysis in postmenopausal women. These results might be interpreted as protection by estrogen against the propagation of thrombi that could result in myocardial ischemia and infarction. On the other hand, coagulation activation and increased risk of thromboemboli and myocardial infarction have also been reported with hormone replacement therapy in postmenopausal women. In an effort to gain a better understanding of the complex effects of estrogen on hemostasis, this chapter will review a number of observational trials and treatment studies conducted in postmenopausal women receiving estrogen therapy.